Image steganography in spatial domain: A survey - Hussain, Mehdi; Wahab, Ainuddin Wahid Abdul; Idris, Mohd Yamani Idna; Ho, Anthony Tung Shuen; Jung, Ki-Hyun (Elsevier, 2018)
This paper presents a literature review of image steganography techniques in the spatial domain for last 5 years. The research community has already done lots of noteworthy research in image steganography. Even though it is interesting to highlight that the existing embedding techniques may not be perfect, the objective of this paper is to provide a comprehensive survey and to highlight the pros and cons of existing up-to-date techniques for researchers that are involved in the designing of image steganographic system. In this article, the general structure of the steganographic system and classifications of image steganographic techniques with its properties in spatial domain are exploited. Furthermore, different performance matrices and steganalysis detection attacks are also discussed. The paper concludes with recommendations and good practices drawn from the reviewed techniques.